BINGKAI HARIAN KOMPAS DALAM PEMBERITAAN PERATURAN PRESIDEN TENTANG TENAGA KERJA ASING - Iswara Pramusita, Regina; Noor Rakhmad, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2020)
The issuance of the Presidential Regulation on Foreign Workers has drawn protests from labor groups because there are three articles that are considered detrimental to Indonesian workers. These articles are considered not in accordance with Labor Law No. 13/2003 . This regulation is also considered to simplify blue collar foreign workers entering Indonesia. This argument arises because the data showed an increase in the number of blue collar foreign workers in Indonesia in 2017. Kompas, one of daily newspaper in Indonesia, also reports this issue. Mass media should carry out its function as social control and provide spaces for all groups of people. However, Kompas tends to provide more spaces for the government as the informants. The choice of informants has influenced Kompas' news. Thus, this research aims to explain how Kompas constructs the news about Presidential Regulation on Foreign Workers. This study uses the Social Construction of Reality Theory which was introduced by Peter L. Berger and Thomas Luckmann. This research is a qualitative descriptive study and uses framing analysis developed by Robert Entman. The results of this research indicate that Kompas uses economic frame in reporting on the Presidential Regulation on the Foreign Workers. Economic news is important because it has a big influence on the human life which is preoccupied by making a living to fulfill their needs. Kompas uses economic frame because the issue of the Presidential Regulation on Foreign Workers intersects with the issue of labor and foreign investment. The economic frame is indicated by the selection of issues and emphasis on certain aspects. Kompas Daily Newspaper chose to present the issue of procedure arrangement to increase Indonesian investment. Another issue presented by Kompas was that public considered the issuance of Perpres No. 20/2018 reduced job opportunities for local workers. Kompas makes certain aspects of an event stand out using positive titles related to the Presidential Regulation on the Foreign Workers. Kompas also displays certain phrases that support the selection of issues. They then highlighted through the selection of positive titles regarding the Presidential Regulation on Foreign Workers as well as the selection of informants who mostly feature government.